B Corporation: the importance of environmental, social and corporate governance - Gonçalves, Margarida Gsapar Franja Franco (2023)
This internship report comes in the scope of the Master’s in Management Control, at Instituto Superior de Contabilidade e Administração de Coimbra. The report, developed in the context of PolyPerception, the start-up where the curricular internship took place, has the goal of proposing improvements to the ESG framework of PolyPerception, by first exploring the importance of environmental, social, and corporate governance in companies. Moreover, intends to research on B Corp Certification, and assess its viability in the context of PolyPerception. The conclusion was that the ESG framework is an important tool for companies to be compliant and demonstrate their focus on sustainable growth, and additionally shows the importance of corporate governance in start-ups, being this a big focus of PolyPerception. Furthermore, the B Corp Certification appears as a differentiator for companies which are considerate of their impact on people and the planet, revelling as a powerful tool for PolyPerception. Even though, these two approaches are promising, it wasn’t possible to analyse the aftermath of implementing these tools, since there wasn’t the space to apply them throughout the internship due to lack of resources in PolyPerception.